Starch accumulation in cassava roots: spatial and temporal distribution - Figueiredo, Priscila Gonzales [UNESP] (2013)
The relationship between starch and morpho-physiology aspects of cassava plant has not been identified. Considering this aspects, the present study showed the temporal and spatial distribution of starch grains in storage roots of cassava, variety IAC 576-70 with 90 and 120 days after planting. From these evaluations, a concentration of starch around the secondary xylem vessels of the cassava tuberous roots was observed, which may be related to the movement of organic solutes in the xylem vessels, water flow and the occurrence of the symptoms of the physiological deterioration in these roots.